Option applications for retailers in a decentralized inventory system. (January 2023) - Feng, Jiejian; Huang, Kai; Zhang, Michael; Castillo, Ignacio; Yang, Jinglei
Abstract: In decentralized inventory systems, consisting of retailers who have private information about future demand, information sharing has been shown to be a potential solution for the retailers to increase their profits. However, since in practice retailers usually pursue individual interests, it is inherently difficult for them to trust each other and to share information well. Here we introduce a standardized modern option as a promising alternative solution that allows retailers to take both competition and collaboration among themselves into account. We develop the optimal decisions on order quantities for retailers in a decentralized system. Highlights: Compare options with information sharing on retailer's view. Determine optimal order quantities under the information sharing policy. Determine optimal order quantities under the option policy.